Isolation of Shigella species and their resistance patterns to a panel of fifteen antibiotics in mid and far western region of Nepal - Khan, Salman (Asian Pacific Tropical Medicine Press, 2014)
OBJECTIVE: To determine the antimicrobial resistance patterns of Shigella species to the most commonly used antibiotics in mid and far western part of Nepal. METHODS: Stool samples were collected from 458 patients who came from mid and far western region of Nepal, attending OPD & IPD Departments of Nepalgunj Medical College, Nepal, between the periods of September 2011 to March 2013. Standard microbiological procedures were used for isolation and identification of Shigella species while the disc diffusion test was used to determine the antimicrobial resistance patterns of the recovered isolates. RESULTS: A total of 65 isolates were identified as Shigella species. Shigella flexneri, Shigella dysenteriae, Shigella boydii and Shigella sonnei were accounted respectively for 43.07%, 27.69%, 21.53% and 7.69% of the total number of Shigella isolated. Resistances to nalidixic acid (95.38%), ampicillin (84.62%), co-trimoxazole (81.54%) and ciprofloxacin (46.15%) were observed. Greater number of isolates (38.46%) was recovered from those aged 1-10 years. This was statistically significant (P<0.05), compared to the other age groups. CONCLUSIONS: The study revealed the endemicity of shigellosis with Shigella flexneri as the predominant serogroup. Children were at a higher risk of severe shigellosis. The results also suggest that nalidixic acid, ampicillin, co-trimoxazole and ciprofloxacin should not be used empirically as the first line drugs in the treatment of shigellosis. Periodic analysis of resistance patterns is necessary for the appropriate selection of empirical antimicrobial therapy.